Communication and Cooperation in Social Dilemmas: A Meta-Analytic Review - BALLIET, Daniel (Institutional Knowledge at Singapore Management University, 2010)
Among the most researched solutions to social dilemmas is communication. Since the late 1950s, it has been well known that communication enhances cooperation in social dilemmas. This article reports a meta-analysis of this literature (forty-five effect sizes) and finds a large positive effect of communication on cooperation in social dilemmas (d = 1.01). This effect is moderated by the type of communication, with a stronger effect of face-to-face discussion ( d = 1.21) compared to written messages (d = 0.46). The communication-cooperation relationship is also stronger in larger, compared to smaller, group social dilemmas. Whether communication occurred before or during iterated dilemmas did not statistically affect the communication-cooperation effect size. Results are discussed according to theory and research on communication in social dilemmas.